Synthesis, characterization, In vitro and In silico investigations of novel 1,2,3-triazole substituted salicylic acid phenolic hydrazones hybrids targeting TGF-β2 expression in colorectal carcinoma - Ay, Ebru Nur; Cakir, Furkan; Akyuz, Sarehan; Kilinc, Namik; Tokali, Feyzi Sinan; Senol, Halil (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2025)
In this study, sixteen novel 1,2,3-triazole-substituted salicylic acid phenolic-hydrazone hybrids were synthesized and characterized using NMR, IR, HRMS, and HPLC techniques. The compounds were evaluated for their anticancer potential against HCT-116, Caco-2 and HT-29 colorectal carcinoma cells and normal BEAS-2B epithelial cells. Among them, compound 10k exhibited potent antiproliferative effects on HCT-116, Caco-2 and HT-29 with IC50 values of 6.84, 10.21, and 9.47 mu M, respectively, which were significantly lower than the reference drug sorafenib (IC50 = 18.25, 13.80 and 7.89 mu M) for HTC-116 and Caco-2. Biological assays demonstrated that 10k effectively downregulated TGF-(32 receptor and cytokine expression in a dose-dependent manner, indicating its role in modulating the TGF-(3 signaling pathway. Apoptosis analysis suggested that cytotoxicity was mediated via non-apoptotic mechanisms. Molecular docking studies revealed a strong binding affinity for compound 10k with a docking score of-11.28 kcal/mol. Furthermore, 250 ns molecular dynamics simulations confirmed the stability of the ligand-receptor complex with an RMSD value stabilized around 1.15 & Aring;. Key interactions included hydrogen bonds with Asn-332, it-it stacking, and halogen bonding. ADMET predictions confirmed favorable drug-like properties with good permeability and safety profiles. These findings position compound 10k as a promising lead candidate for colorectal cancer therapy, targeting TGF-(32 mediated pathways with high efficacy and selectivity.
Keywords: 1,2.3-Triazoles; Hydrazone; Colorectal cancer; TGF-beta 2; Molecular docking; TGF-BETA; DERIVATIVES; Pharmacology & Pharmacy